Use of unmanned aerial vehicles in monitoring application and management of natural hazards - Giordan, D. (2020)
The recent development of unmanned aerial vehicles (UAVs) has been increasing the number of technical solutions that can be used to monitor and map the effects of natural hazards. UAVs are generally cheaper and more versatile than traditional remote-sensing techniques, and they can be therefore considered as a good alternative for the acquisition of imagery and other physical parameters before, during and after a natural hazard event. This is an important added value especially for investigations over small areas (few km2). In the special issue ‘The use of Unmanned Aerial Vehicles in monitoring application and management of natural hazards’, we collected a number of case studies, aiming at providing a range of applications of monitoring and management of natural hazards assessed through the use of UAVs.